2006
DOI: 10.1016/j.diabres.2005.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome in Spanish migrants to Brazil: Unexpected results

Abstract: A cross-sectional study was performed involving epidemiological and clinical features of the metabolic syndrome (MS) in Spanish migrants to Brazil and their descendants. This included 479 subjects: Group A (Spanish migrants): n=215; Group B (descendants born in Brazil of Spanish parents): n=126, Group C (mixed descendants born in Brazil with either father or mother born in Spain): n=138. MS was defined according to the original NCEP/ATP III criteria and by the revised NCEP/ATP definition (glucose>or=100mg/dl).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…In Latin America, the prevalence of MS among adults ranges from 20 to 50% depending on the age group, gender and particular characteristics of the population studied (18,19,24,25). In Brazil, data from most epidemiological studies are restricted to specific population groups (20,(26)(27)(28)(29)(30), a fact that impairs comparisons. The MS prevalence observed in the present study is higher than recently reported, a fact that may be attributable to the lower age of the group studied in 1999-2000, which included people from 25 to 64 years of age (21).…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, the prevalence of MS among adults ranges from 20 to 50% depending on the age group, gender and particular characteristics of the population studied (18,19,24,25). In Brazil, data from most epidemiological studies are restricted to specific population groups (20,(26)(27)(28)(29)(30), a fact that impairs comparisons. The MS prevalence observed in the present study is higher than recently reported, a fact that may be attributable to the lower age of the group studied in 1999-2000, which included people from 25 to 64 years of age (21).…”
Section: Discussionmentioning
confidence: 99%
“…Given the interaction between prenatal and postnatal conditions in influencing risk and the rapid rate at which environmental, and particularly nutritional, conditions are changing throughout the world, the fetal programming hypothesis has particularly worrisome public health implications Gluckman et al, In press). Studies of migrant populations from developing to developed countries indicate that a dramatic shift in the nutritional environment between gestation, childhood, and adult life may underlie the elevated risk for heart disease and diabetes that such populations face (Barnett et al, 2006;Beaulieu et al, 2007;Candib, 2007;Daryani et al, 2005;Dwivedi, Agarwal, Suthar, and Dwivedi, 2004;Foucan et al, 2006;Lob-Corzilius, 2007;Misra and Misra, 2003;Misra and Vikram, 2004;Misra, Endemann, and Ayer, 2005;Pousada et al, 2006;Schwingel et al, 2007;Trayhurn, 2005;Tull, Thurland, and LaPorte, 2005). Rapid nutritional transitions in the developing world may be accompanied by similar increase in chronic disease burden, if the fetal programming principle holds true.…”
Section: Fetal Programming In Human Epidemiologymentioning
confidence: 99%
“…Agreement between the two criteria was only modest (kappa coefficient 0.28-0.57) [88]. Furthermore, a cross-sectional study in Spanish migrants to Brazil showed that the overall prevalence of the MetS according to the NCEP ATP III criteria was 26.3% (age/sex-adjusted prevalence 27.4 %) [89]. When the revised NCEP ATP III criteria (glucose ≥ 5.6 mmol/l; 100 mg/dl) were applied the overall prevalence was 30.1% (age/sex-adjusted 31.3%).…”
Section: Selected Studies Comparing the Diffe-rent Definitionsmentioning
confidence: 96%
“…When the revised NCEP ATP III criteria (glucose ≥ 5.6 mmol/l; 100 mg/dl) were applied the overall prevalence was 30.1% (age/sex-adjusted 31.3%). The differences between the two criteria were 3.8% and 3.9% (overall and age/sexadjusted prevalence, respectively) [89]. In another study [90] the associations between three definitions of the MetS (IDF, WHO, NCEP ATP III) and coronary heart disease risk was evaluated in a prospective cohort study of a random sample of 3,589 British women, aged 60-79 years old and free of coronary heart disease at baseline.…”
Section: Selected Studies Comparing the Diffe-rent Definitionsmentioning
confidence: 99%